ANTICOAGULANT THERAPY FOR CHRONIC KIDNEY DISEASE AND ATRIAL FIBRILLATION: THE AXIS OF ROTATION BETWEEN THE POLES OF RISK - Z. D. Kobalava; A. A. Shavarov (Евразийский Кардиологический Журнал, 2018)
The frequent comorbidity of atrial fibrillation (AF) and chronic kidney disease (CKD) in the general population is demonstrated in many epidemiological studies. Most patients with an established diagnosis of AF are recommended to use constant anticoagulant therapy (ACT) to prevent ischemic stroke and thromboembolic complications (TEC). With renal dysfunction, changes in the hemostatic system are observed at all stages of CKD, both related to an increase in prothrombogenic activity as well as to development of coagulopathy, which increases the threat of bleeding. Therefore, in patients with CKD and AF, an important aspect of ACT is the choice of the optimal anticoagulant, that will provide a balance between the risks of stroke and hemorrhagic complications, to which this article is dedicated.